Rizzoli & Isles. the complete third season [videorecording (DVD)] - Gerritsen, Tess; Harmon, Angie, 1972-; Alexander, Sasha, 1973-; Bridges, Jordan, 1973-; Young, Lee Thompson, 1984-2013; McGill, Bruce, 1950-; Bracco, Lorraine, 1955- (Rizzoli & Isles, 2013)
When an explosive misstep drives a painful wedge between Boston's finest crime-solving colleagues, Jane and Maura must set aside their personal difficulties in order to keep on top of the city's most heinous murder cases. Yet analyzing corpses and tracking killers is child's play compared to the complications that arise from both friends' families. Using intellect & instinct, the best friends do what it takes to regain each other₂s trust while busting criminals in all 15 witty, gritty episodes.